Cost-effectiveness of sacituzumab govitecan in hormone receptor-positive/human epidermal growth factor receptor 2-negative metastatic breast cancer - Shi, Demin; Li, Yan; Liang, Xueyan; Chen, Lingyuan (Frontiers in Oncology, 2023)
Background The efficiency and safety of sacituzumab govitecan (SG) for the therapy of hormone receptor-positive (HR+)/human epidermal receptor 2-negative (HER2-) metastatic breast cancer (BC) has been demonstrated. The aim of this study is to evaluate its cost-effectiveness on HR+/HER2- metastatic BC from the third-party payer perspective in the United States. Methods We performed the cost-effectiveness of SG and chemotherapy using a partitioned survival model. TROPiCS-02 provided clinical patients for this study. We evaluated the robustness of this study by one-way and probabilistic sensitivity analyses. Subgroup analyses were also conducted. The outcomes were costs, life-years, quality-adjusted life years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefit (INHB), and incremental net monetary benefit (INMB). Results SG treatment was related to an increase of 0.284 life years and 0.217 QALYs over chemotherapy, as well as a cost increase of $132,689, reaching an ICER of $612,772/QALY. The INHB was -0.668 QALYs, and the INMB was -$100,208. SG was not cost-effective at the willingness to pay (WTP) threshold of $150,000/QALY. The outcomes were sensitive to patient body weight and cost of SG. SG may be cost-effective at the WTP threshold of $150,000/QALY if the price is less than $3.997/mg or the weight of patients is under 19.88 kg. Based on the subgroup analysis, SG did not prove cost-effective in all subgroups at the WTP threshold of $150,000/QALY. Conclusion From a third-party payer standpoint in the United States, SG was not cost-effective, even though it had a clinically significant advantage over chemotherapy for the treatment of HR+/HER2- metastatic BC. The cost-effectiveness of SG can be improved if the price is substantially reduced.